Development of transcriptomic tools for predicting the response to individual drug of the mFOLFIRINOX regimen in patients with metastatic pancreatic cancer - Fraunhoffer, Nicolas; Teyssedou, Carlos; Pessaux, Patrick; Bigonnet, Martin; Dusetti, Nelson; Iovanna, Juan (Frontiers in Oncology, 2024)
BackgroundThe utilization of modified FOLFIRINOX (mFFX) therapy has shown notable advancements in patient outcomes in both localized and metastatic PDAC. Nevertheless, the effectiveness of mFFX treatment comes at the cost of elevated toxicity, leading to its restriction to patients with adequate performance status. Consequently, the administration of mFFX is contingent upon patient performance rather than rational criteria. The ideal scenario would involve the ability to assess the sensitivity of each drug within the mFFX regimen, minimizing unnecessary toxicity without compromising clinical benefits.MethodsWe developed transcriptomic signatures for each drug of the mFFX regimen (5FU, oxaliplatin and irinotecan) by integrating transcriptomic data from PDC, PDO and PDX with their corresponding chemo-response profiles to capture the biological components responsible for the response to each drug. We further validated the signatures in a cohort of 167 patients with advanced and metastatic PDAC.ResultsAll three signatures captured high responder patients for OS and PFS in the mFFX arm exclusively. We then studied the response of patients to 0, 1, 2 and 3 drugs and we identified a positive correlation between the number of drugs predicted as sensitive and the OS and PFS, and the with objective response rate.ConclusionsWe developed three novel transcriptome-based signatures which define sensitivity for each mFFX components that can be used to rationalize the administration of the mFFX regimen in patients with metastatic pancreatic cancer and could help to avoid unnecessary toxic effects.